2022
DOI: 10.1001/jamanetworkopen.2022.16341
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Risk Factors Associated With Stroke Recurrence in China, 2007-2018

Abstract: IMPORTANCERecurrent stroke rates have decreased substantially in Western countries. However, data on changes in stroke recurrence and risk factor patterns in China are limited. OBJECTIVE To systematically assess stroke recurrence trends by evaluating temporal improvement in guideline-recommended secondary prevention treatment performance and changes in risk factor patterns over 10 years in China. DESIGN, SETTING, AND PARTICIPANTS This post hoc cohort study was conducted based on data from the China National St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 42 publications
2
29
1
1
Order By: Relevance
“…Cardio-cerebrovascular disease is one of the most serious diseases that threaten human health today; its morbidity and mortality rates have surpassed those of tumor diseases and now rank first (Liberale et al, 2021;Xu et al, 2022). The heart and brain are the most closely related organs physiologically, and brain tissue relies on blood circulation driven by the heart to maintain normal physiological functions.…”
Section: Introductionmentioning
confidence: 99%
“…Cardio-cerebrovascular disease is one of the most serious diseases that threaten human health today; its morbidity and mortality rates have surpassed those of tumor diseases and now rank first (Liberale et al, 2021;Xu et al, 2022). The heart and brain are the most closely related organs physiologically, and brain tissue relies on blood circulation driven by the heart to maintain normal physiological functions.…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic stroke and transient ischemic attack (TIA) are characterized by early recurrence, which may be fatal or disabling. The rate of recurrent stroke is reported to be around 10% within 3 months after the index event [ 1 , 2 , 3 ]. Early identification of patients at high-risk of recurrence is of clinical importance.…”
Section: Introductionmentioning
confidence: 99%
“…Using the China National Stroke Registries (CNSRs) for 2007 to 2008 (CNSR I) and 2015 to 2018 (CNSR III), Xu and colleagues systematically assessed changes in the rate of stroke recurrence in a Chinese population and found that cumulative incidence of recurrent stroke within 12 months decreased from 15.5% to 12.5% over 10 years. Interestingly, this outcome was accompanied by the finding that use of secondary preventive medications increased markedly in the past decade in China.…”
mentioning
confidence: 99%
“…Based on this finding, the authors hypothesized that there may have been suboptimal control of traditional risk factors or lack of awareness and management of potential new risk factors. To test the hypothesis, Xu and colleagues assessed the risk factor patterns for recurrent stroke by comparing data from CNSR III with those from CNSR I. They found that over the course of 10 years, age, prior stroke, coronary heart disease, higher National Institutes of Health Stroke Scale score, and higher low-density lipoprotein cholesterol (LDL-C) levels remained risk factors associated with stroke recurrence.…”
mentioning
confidence: 99%
See 1 more Smart Citation